Structure and properties of intermetallics in pre-transitional low-stability states - Potekaev, A. I. (Alexandr I.); Glezer, A. M. (Aleksandr Markovich); Kulagin, V. V.; Starostenkov, M. D.; Klopot, A. A. (Boca Raton : CRC Press, 2020)
This book is dedicated to the fundamental physical aspects of stability, the influence of structural defects on the properties and structural phase transformations of BCC alloys. The authors present patterns that occur in the structural-phase states of functional alloys with low stability or instability under thermal cycling effects. Structural-phase transformations and the physical laws governing the influence of the thermomechanical effect on the properties of alloys are examined to advance development of technological processes for processing functional materials. Features: Studies the correlation between structural phase states and changes in the physico-mechanical properties of intermetallic compounds Explores the influence of thermomechanical cycling on the properties of functional alloys Details low-stability pretransition states in alloys
Features of pretransition low-stability structural phase states of bcc alloys during thermal cycling. The effect of various factors on the low-stability pretransitional structural phase states of the NiAl intermetallic compound. Pre-transition low-stability states in TiNi-based alloys. The effect of structural defects, low-stability pretransition states and phase-structural transformations on the stability of alloys. References. Index.
OCLC-licensed vendor bibliographic record.
Keywords: Intermetallic compounds -- Testing; Alloys -- Testing; Intermetallic compounds -- Thermal properties; TECHNOLOGY / Metallurgy; TECHNOLOGY / Engineering / Chemical & Biochemical; SCIENCE / Solid State Physics